Development of string-shaped radiophotoluminescence dosimeter for high-radiation field. (April 2018) - Sato, Fuminobu; Hashimoto, Taichi; Tamaki, Shingo; Kusaka, Sachie; Miyamaru, Hiroyuki; Murata, Isao
Abstract: We developed a long and bendable string-shaped dosimeter, 2 mm in diameter. This string-shaped dosimeter, which was made from a mixture of silver-activated metaphosphate glass particles and polylactic acid resin, was fabricated with a filament extruder. The maximum ratio of glass to resin by weight was 20%. The photoluminescence spectra had absorbed-dose-dependent peaks at 635 nm. At doses above 50 Gy, orange photoluminescence could be observed with the naked eye. A one-dimensional (1-D) readout system for string-shaped dosimeters comprised an ultraviolet (UV)-LED, a photodiode, and a drawing machine. In a preliminary experiment, a string-shaped dosimeter was uniformly exposed to 60 Co gamma rays. The position dependency of the detection efficiency of the string-shaped dosimeter was investigated, and its coefficient of deviation was approximately 4%. The string-shaped dosimeter was partly exposed to X-ray beams. The 1-D dose profile of the string-shaped dosimeter was successfully obtained by the readout system. The radiophotoluminescence response was sufficiently related with the absorbed dose in a dose range up to 500 Gy. The spatial resolving power (FWHM) was approximately 3 mm, owing to the width of the slit for the UV illuminator in the readout system. These results indicated that the string-shaped dosimeter was useful in 1-D dose measurement of the high-radiation field. Highlights: We developed a new string-shaped dosimeter for high-dose dosimetry. The string-shaped dosimeter was made from a mixture of RPL glass and PLA resin. A 1-D dose measurement was successfully performed with the string-shaped dosimeter. The spatial resolving power in the 1-D dose measurement was approximately 3 mm.